2003
DOI: 10.1046/j.1365-3083.2003.01211.x
|View full text |Cite
|
Sign up to set email alerts
|

T‐ and B‐Cell Epitopes in the Secreted Mycobacterium bovis Antigen MPB70 in Mice

Abstract: MPB70 is a soluble secreted protein highly expressed in Mycobacterium bovis and strains of bacille Calmette±Gue Ârin (BCG); as such, it is a candidate for subunit and DNA vaccines against tuberculosis. MPB70 was screened for T-cell epitopes in four different inbred mouse strains. Major histocompatibility complex (MHC) H-2 b -expressing mice (C57BL/6) secreted interferon-g (IFN-g) after stimulation with peptides from the regions 1±20, 41±50, 81±110, 121±150 and 161±193 of the MPB70 sequence. H-2 db mouse (B6D2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…, 1987; Fifis et al ., 1994; Roche et al ., 1994; Harboe et al ., 1995; Wiker et al ., 1996; Vordermeier et al ., 2000; Lyashchenko et al ., 2001). Based on these observations, both MBP70 and MPB83 have been developed as candidates for novel TB vaccine development (Chambers et al ., 2000; Morris et al ., 2000; Al Attiyah et al ., 2003; Tollefsen et al ., 2003; Xue et al ., 2004). As extracellular antigens have consistently been implicated in the induction of a protective immune response against M. tuberculosis , it is remarkable that all BCG strains are unable to produce the antigenic proteins ESAT‐6 and CFP‐10 (lost with the RD1 deletion of 1908–1921), while strains obtained after 1927–1931 are also deficient (through the deletion of RD2) in the proteins MPB64 (Harboe et al ., 1986; Li et al ., 1993) and CFP‐21 (Mahairas et al ., 1996; Weldingh et al ., 1998; Weldingh and Andersen, 1999) and functionally deficient in production of MPB70 and MPB83 via the sigK mutation described here.…”
Section: Discussionmentioning
confidence: 99%
“…, 1987; Fifis et al ., 1994; Roche et al ., 1994; Harboe et al ., 1995; Wiker et al ., 1996; Vordermeier et al ., 2000; Lyashchenko et al ., 2001). Based on these observations, both MBP70 and MPB83 have been developed as candidates for novel TB vaccine development (Chambers et al ., 2000; Morris et al ., 2000; Al Attiyah et al ., 2003; Tollefsen et al ., 2003; Xue et al ., 2004). As extracellular antigens have consistently been implicated in the induction of a protective immune response against M. tuberculosis , it is remarkable that all BCG strains are unable to produce the antigenic proteins ESAT‐6 and CFP‐10 (lost with the RD1 deletion of 1908–1921), while strains obtained after 1927–1931 are also deficient (through the deletion of RD2) in the proteins MPB64 (Harboe et al ., 1986; Li et al ., 1993) and CFP‐21 (Mahairas et al ., 1996; Weldingh et al ., 1998; Weldingh and Andersen, 1999) and functionally deficient in production of MPB70 and MPB83 via the sigK mutation described here.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, different species and even different breeds of the same species can develop diverse immune responses after vaccination with the same antigens. For example, it has been reported that mice of H-2 b and H2 d haplotype can develop Th1and Th2-type responses, respectively, after BCG vaccination [34,35]. Secondly, the balance between cellular and humoral immune responses induced following vaccination or infection could also be influenced by the nature of the antigens.…”
Section: Discussionmentioning
confidence: 99%
“…In order to fight against the TB, the development of the mediated immune response by cytotoxic Th1 CD4+ and T CD8+ of the IFN- (Tollefsen et al, 2003) is essential. The development of anergy and reduction in the number of T cells CD4+ in patients with viral diseases contribute to the susceptibility to TB (Bouchonnet et al, 2002).…”
Section: T Cells (T Cells Cd4 and T Cells Cd8)mentioning
confidence: 99%